The Hidden Link between Motivations Driving Earnings Management and Capital Structure Decisions: A Bibliometric Perspective - Milda Striupaitytė; Anastasiia Niesheva (Buhalterinės Apskaitos Teorija ir Praktika)
In this paper, earnings management and capital structure decisions are analysed from a new perspective. Bibliometric analysis of the link between capital structure and earnings management is performed, providing new insights on historical evolution of research in the field. The links between keywords in the research area are analysed and grouped in clusters. Valuable insights on the level of research carried out in the field are presented. Current studies are expanded by adding theoretical background analysis: capital structure decisions and the motives of earnings management are compared in the context of various theories. In this paper, common incentives behind capital structure decisions and earnings management are revealed. Systematic comparison between capital structure decisions and motives of earnings management together with results of bibliometric analysis provide new insights on the topic and can assist in future research.